COPA DO MUNDO: DO JOGO DE FUTEBOL AO NEGÓCIO TURÍSTICO - Rogerio do Amaral (Universidade do Oeste Paulista, 2007)
The present article aims to discuss the link between the World Cup end the Events Tourism, having the goal to analyze how that event helps the local tourists' zone, in infra-structure issues and also in advertising the place abroad, aiming the reception of visitors after the end of the sports event.